Access to care through telehealth among U.S. Medicare beneficiaries in the wake of the COVID-19 pandemic - Lu, Min; Liao, Xinyi (Frontiers in Public Health, 2022)
Background The coronavirus disease 2019 (COVID-19) public health emergency has amplified the potential value of deploying telehealth solutions. Less is known about how trends in access to care through telehealth changed over time. Objectives To investigate trends in forgone care and telehealth coverage among Medicare beneficiaries during the COVID-19 pandemic. Methods A cross-sectional study design was used to analyze the outcomes of 31,907 Medicare beneficiaries using data from three waves of survey data from the Medicare Current Beneficiary Survey COVID-19 Supplement (Summer 2020, Fall 2020, and Winter 2021). We identified informative variables through a multivariate classification analysis utilizing Random Forest machine learning techniques. Findings The rate of reported forgone medical care because of COVID-19 decreased largely (22.89% to 3.31%) with a small increase in telehealth coverage (56.24% to 61.84%) from the week of June 7, 2020, to the week of April 4 to 25, 2021. Overall, there were 21.97% of respondents did not know whether their primary care providers offered telehealth services; the rates of forgone care and telehealth coverage were 11.68% and 59.52% (11.73% and 81.18% from yes and no responses). Our machine learning model predicted the outcomes accurately utilizing 43 variables. Informative factors included Medicare beneficiaries’ age, Medicare-Medicaid dual eligibility, ability to access basic needs, certain mental and physical health conditions, and interview date. Conclusions This cross-sectional survey study found proliferation and utilization of telehealth services in certain subgroups during the COVID-19 pandemic, providing important access to care. There is a need to confront traditional barriers to the proliferation of telehealth. Policymakers must continue to identify effective means of maintaining continuity of care and growth of telehealth services.